Answer:
if the sum of two angles is 90° they are said to be complementary
If one angle is x
the other should be (90 - x)°
so the complementary angle of x is (90 - x)
Answer:
12,8
Step-by-step explanation:
Just line them up and you will arrive at your answer:
5,8
+ 7
_____
12,8
I am joyous to assist you anytime.
The main purpose of the passage is to describe the purpose, methods, and results of an experiment. The correct option is B.
Given a passage shown in the attached pictures.
Option B is the best answer. The first paragraph of the passage identifies and describes "Texas squash vines" (line 1), but the main focus of the passage is introduced in the first sentence of the second paragraph. The remainder of the passage focuses on describing the purpose, process, and results of recent research conducted on these Texas squash vines.
Option A is incorrect because the passage doesn’t focus on the assumptions behind a theory but rather on the way in which that theory was tested. Option C is incorrect because the passage does not contain a lot of conflicting data; most of them support the idea that there may be too many scents for the Texas squash. Option D is incorrect because the passage explains the procedures used in a study were “’very labor intensive’” (line 58) but does not present them as particularly innovative.
Hence, the primary purpose from the given passage is to describe the aim, method, and results of an experiment.
Learn more about the passage from here brainly.com/question/12555695
#SPJ4
Answer:
∠L = 43°
∠M = 121°
∠N = 16°
Step-by-step explanation:
<u>Start by setting all sides equal to 180</u>
3x - 5 + 7x + 9 + x = 180
<u>Add like terms</u>
11x + 4 = 180
<u>Solve for x</u>
11x + 4 = 180
- 4 - 4
11x = 176
/ 11 /11
x = 16
<u>Now, plug in 16 for all instances of x on the triangle and solve.</u>
∠L = 43°
∠M = 121°
∠N = 16°
<u>Define x:</u>
Let the first number be x.
1st number = x
2nd number = x + 1
3rd number = x + 2
<u>Construct equation:</u>
x + x + 1 + x + 2 = 4(x + 1)
3x + 3 = 4(x + 1)
Answer: 3x + 3 = 4(x + 1)